The psychological well-being during the COVID-19 lockdown of doctoral students at a private higher education institution in South Africa: An application of Self-Determination Theory - Hoque, M. (South African Journal of Higher Education, 2024)
Doing a doctorate can be an experience but it can also be challenging. Doctoral students often experience high levels of stress, pressure, and expectations, which can have a negative impact on their mental health. There is very little research examining the psychological well-being of doctoral students during COVID-19 in the South African context. This study therefore aimed to assess the psychological well-being of doctoral students at a private South African university. A cross-sectional study was conducted with forty-two doctoral students, using a self-completed and validated questionnaire. The data were collected using the QuestionPro online platform. The significant predictor for positive emotion was identified using multiple of linear regression analysis using SPSS version 27.0. Most of the participants agreed highly regarding relatedness, autonomy and competence. Autonomy and competence are significant predictors of positive emotions. This study highlights the importance of perceived competence, autonomy, and positive emotions for the psychological well-being of doctoral students during unplanned and involuntary periods of remote learning. The findings provide insights into approaches that might be employed to enhance the well-being of doctorate students through distant learning, hence minimising the adverse consequences of this particular circumstance.